Distinguishing Multisystem Inflammatory Syndrome in Children From COVID-19, Kawasaki Disease and Toxic Shock Syndrome. Issue 4 (27th January 2022) - Godfred-Cato, Shana; Abrams, Joseph Y.; Balachandran, Neha; Jaggi, Preeti; Jones, Kaitlin; Rostad, Christina A.; Lu, Austin T.; Fan, Lucie; Jabbar, Aysha; Anderson, Evan J.; Kao, Carol M.; Hunstad, David A.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Distinguishing multisystem inflammatory syndrome in children (MIS-C) from coronavirus disease 2019 (COVID-19), Kawasaki disease (KD), and toxic shock syndrome (TSS) can be challenging. Because clinical management of these conditions can vary, timely and accurate diagnosis is essential. Methods: Data were collected from patients <21 years of age hospitalized with MIS-C, COVID-19, KD, and TSS in 4 major health care institutions. Patient demographics and clinical and laboratory data were compared among the 4 conditions, and a diagnostic scoring tool was developed to assist in clinical diagnosis. Results: A total of 233 patients with MIS-C, 102 with COVID-19, 101 with KD, and 76 with TSS were included in the analysis. Patients with MIS-C had the highest prevalence of decreased cardiac function (38.6%), myocarditis (34.3%), pericardial effusion (38.2%), mitral regurgitation (31.8%) and pleural effusion (34.8%) compared with patients with the other conditions. Patients with MIS-C had increased peak levels of C-reactive protein and decreased platelets and lymphocyte nadir counts compared with patients with COVID-19 and KD and elevated levels of troponin, brain natriuretic peptide and pro-brain natriuretic peptide compared with COVID-19. Diagnostic scores utilizing clinical findings effectively distinguished MIS-C from COVID-19, KD, and TSS, with internal validation showing area under the curve ranging from 0.87 to 0.97. Conclusions: Compared with COVID-19, KD, and TSS, patients with MIS-C had significantly higher prevalence of cardiac complications, elevated markers of inflammation and cardiac damage, thrombocytopenia, and lymphopenia. Diagnostic scores can be a useful tool for distinguishing MIS-C from COVID-19, KD, and TSS.